Genotype-phenotype relationships as prognosticators in Rett syndrome should be handled with care in clinical practice - Halbach, Nicky S.J.; Smeets, Eric E.J.; van den Braak, Noortje; van Roozendaal, Kees E.P.; Blok, Rien M.J.; Schrander-Stumpel, Constance T.R.M.; Frijns, Jean-Pierre; Maaskant, Marian A.; Curfs, Leopold M.G. (American journal of medical genetics. Part A, 2012)
Rett syndrome (RTT; OMIM 312750) is an X‐linked dominant neurodevelopmental disorder leading to cognitive and motor impairment, epilepsy, and autonomic dysfunction in females. Since the discovery that RTT is caused by mutations in MECP2, large retrospective genotype–phenotype correlation studies have been performed. A number of general genotype–phenotype relationships were confirmed and specific disorder profiles were described. Nevertheless, conflicting results are still under discussion, partly due to the variability in classification of mutations, assessment tools, and structure of the data sets. The aim of this study was to investigate relationships between genotype and specific clinical data collected by the same experienced physician in a well‐documented RTT cohort, and evaluate its prognostic value in counseling young parents with a newly diagnosed RTT girl regarding her future outcome. The Maastricht–Leuven Rett Syndrome Database is a register of 137 molecularly confirmed clinical RTT cases, containing both molecular and clinical data on examination and follow up by the same experienced physician. Although the general genotype–phenotype relationships were confirmed, the clinical severity was still found to be very variable. We therefore recommend caution in using genotype–phenotype data in the prognosis of outcome for children in Rett syndrome. Early diagnosis, early intervention, and preventive management are imperative for better outcomes and better quality of daily life for RTT females and their families. © 2011 Wiley Periodicals, Inc.